Clinical and immunological parameters of Newcastle disease vaccination in juvenile ring - necked pheasants (Phasianus colchicus) - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos; Caron, Luiz Felipe; Fernandes Filho, Tobias; Agustini, Marcelo; Ventura, Henrique Larsen Brunow; Doretto Júnior, Luciano (My University, 2008)
Clinical and immunological parameters of vaccinated ring-necked pheasants against Newcastle disease were evaluated. Sixty young birds were distributed into four different experimental groups, vaccinated or not against Newcastle disease (ND): G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain) and G4 (nonvaccinated -control). The immune response was evaluated by the HI test. The vaccinations of pheasants with NDV Ulster 2C, B1 and LaSota strains did not cause any clinical signs associated with post-vaccinal reactions and were similar in the humoral immune response stimulus (HI). © Asian Network for Scientific Information, 2008.
Keywords: B1 and LaSota strains; Newcastle disease; Ring - necked pheasant; Ulster 2C; Vaccination; Aves; Newcastle disease virus; Phasianidae; Phasianus colchicus